Maximum tolerated activity estimation based on red marrow dose using multiple dosimetry approaches in radioiodine therapy surrogated by iodine-124 - Han, Ng Yi (Universiti Sains Malaysia, 2024)
Pre-therapeutic blood-based dosimetry assessment serves as an alternative to the empirical dosage protocol of radioiodine (131I) therapy for treating differentiated thyroid cancer (DTC) patients with a typical condition. It aims to customize a more effective personalized maximum tolerated activity (MTA) of 131I by estimating and ensuring that the resulting absorbed dose in either the blood or red marrow (DBL or DRM) remains within 2 Gy to prevent myelotoxicity. Currently, the Institute Kanser Negara (IKN) relies exclusively on the EANM blood-based dosimetry approach for estimating DBL. This study seeks to compare this approach with three other approaches that have not been previously explored in terms of their correlation and significant differences. Methods: The demographic, dosimetry data and PET/CT images of 12 adult DTC patients who underwent the pre-therapeutic blood-based dosimetry assessment of 131I therapy were retrieved for the dose computation in this retrospective study. Dosimetry approaches include the image-based, red marrow-based and simplified image-based approaches. Results: Both image-based (r = 0.194) and simplified image-based approaches (r = 0.194) demonstrated weak positive correlations while RM-based approach displayed a strong positive correlation (r = 0.540) when compared to blood dose per activity yield by EANM blood-based approach. However, none of these correlations were statistically significant, as indicated by Spearman’s rank correlation test (p>0.05). When evaluating MTA values, both the image-based and RM-based approaches displayed significant disparities compared to the EANM blood-based approach, with p-values of 0.015 and 0.013, respectively. Conversely, the simplified image-based approach demonstrated no statistically significant difference in estimated MTA compared to the EANM blood-based approach, supported by the Mann-Whitney test (p>0.05). Conclusion: It is recommended for IKN to adopt the image-based approach as the standard formalism under all circumstances due to its sensitivity in estimating personalized MTA and ensuring radiation safety.